KAIDAH FIQH BIDANG MU’AMALAH MAZHAB SYAFI’I (Kajian Teoritis dan Praktik serta Kehujjahannya) - Sumarjoko Sumarjoko; Hidayatun Ulfa (Universitas Wahid Hasyim Semarang, 2019)
Abstract The Islamic economic system is believed to be the way of salvation. This will replace the capitalist and socialist economic systems which are considered to be unable to provide a sense of justice and prosperity. To meet and answer the challenge, Islamic jurists (fuqaha) in various layers carried out a methodological study of Islamic law, critical of the manhaj (method) that classical scholars have formulated. The jurists acknowledged, that, legal texts were limited, while new legal cases were constantly developing